Efficient austenitic stainless steel degaussing cooperative treatment method
Through the comprehensive methods of chemical composition regulation, solid solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment, the problems of high energy consumption and unstable effect in the demagnetization treatment of 304 austenitic stainless steel are solved, and the effects of low magnetic properties and high uniformity are achieved, meeting the strict requirements of high-end equipment.
Patent Information
- Application Number
- CN202411975149.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing 304 austenitic stainless steel demagnetization treatment technology has high energy consumption, long processing time, and difficult to accurately control the cooling rate, resulting in changes in the microstructure of the material, affecting the stability of the demagnetization effect, and cannot meet the requirements of high-precision application scenarios.
Using a combination of chemical composition regulation, solid solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment, the austenite structure is stabilized through the synergistic action of nitrogen and manganese elements, and the solid solution treatment makes the elements evenly distributed, and the ultrasonic and electromagnetic field composite demagnetization treatment achieves uniform magnetic reduction.
It achieves low magnetic properties and high uniformity of 304 austenitic stainless steel, and the magnetic strength can be reduced to 0.03Gs-0.12Gs, meeting the strict requirements for magnetism of high-end equipment, ensuring the normal operation and high-precision performance of the equipment, while maintaining other excellent properties of the material.
Smart Images

Figure CN119776722A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of austenitic stainless steel manufacturing, and in particular relates to a high-efficiency austenitic stainless steel demagnetization collaborative processing method. Background Art
[0002] 304 austenitic stainless steel is widely used in many fields such as chemical industry, food processing, medical equipment, architectural decoration, etc. due to its excellent corrosion resistance, good processing formability and relatively reasonable cost. However, in specific fields that are sensitive to magnetism, such as electronic semiconductor manufacturing, ultra-high precision electronic equipment, and high-end medical equipment, its magnetic performance has become a key factor limiting its further application.
[0003] The current demagnetization treatment technologies for 304 austenitic stainless steel mainly include traditional methods such as thermal demagnetization and AC demagnetization. The principle of thermal demagnetization is based on heating the material above the Curie point and then slowly cooling it to disorder the magnetic domains to achieve demagnetization. However, this method has the disadvantages of extremely high energy consumption, lengthy processing time, and difficulty in accurately controlling the cooling rate during the cooling process, which can easily lead to changes in the microstructure of the material, such as uneven grain growth and residual stress, which in turn affects other properties of the material and ultimately leads to unstable demagnetization effects. It is difficult to meet the strict requirements of high-precision application scenarios.
[0004] The AC demagnetization method is to place the material in an alternating magnetic field and gradually reduce the magnetic field strength to zero to achieve demagnetization. However, for 304 austenitic stainless steel parts with complex shapes, the alternating magnetic field is unevenly distributed, resulting in large differences in the magnetic field strength at different parts, uneven demagnetization effect, and difficulty in reducing the magnetism to the extremely low level required by some ultra-high precision equipment, which cannot meet the strict requirements for magnetic accuracy. Summary of the invention
[0005] In view of this, the present invention aims to propose an efficient austenitic stainless steel demagnetization synergistic treatment method, which adopts a combination of chemical composition regulation, solid solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment, which can not only completely solve the magnetic problem, but also ensure that other key properties of the material are not affected, so as to meet the growing demand for high-precision and high-performance applications and enhance the competitiveness and applicability of 304 austenitic stainless steel in the high-end market.
[0006] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0007] A highly efficient austenitic stainless steel demagnetization collaborative treatment method, the method comprising the following steps:
[0008] S1. Chemical composition regulation
[0009] Accurate chemical composition analysis of 304 austenitic stainless steel was performed to control the nitrogen content to 0.1-0.2wt% and the manganese content to 1.4-1.5wt%. Nitrogen and manganese work together to stabilize the austenite structure and inhibit the formation of magnetic phases such as ferrite and martensite, thereby optimizing the initial magnetic properties of the material for subsequent processing.
[0010] S2. Solution treatment
[0011] The 304 austenitic stainless steel regulated by S1 is placed in a vacuum heat treatment furnace to increase the temperature, and then kept warm after reaching the target temperature. During the heat preservation process, various elements (including nitrogen and manganese added in the form of manganese nitride) can be fully dissolved and evenly distributed in the austenite matrix, further reducing the magnetism while maintaining other excellent properties of the material; after the heat preservation is completed, high-purity nitrogen is used for rapid cooling; this cooling method helps to obtain better strength while ensuring the performance of the material, and can effectively avoid the problem of excessive residual stress;
[0012] S3, ultrasonic and electromagnetic field composite demagnetization treatment
[0013] Place the 304 austenitic stainless steel treated with S2 in a composite demagnetization device with ultrasound and electromagnetic field. Select the appropriate ultrasonic transducer and electromagnetic coil layout according to the shape of the component to ensure that the ultrasound and electromagnetic field energy evenly cover the component and keep the ultrasound and electromagnetic field working together for 30min-50min.
[0014] Further, in S2, the temperature is raised to 1050°C-1150°C at a heating rate of 3.5°C / min-4.5°C / min, and kept at this temperature for more than 90 minutes.
[0015] Furthermore, in S2, the cooling rate is 8°C / s-12°C / s; the reasonable control of this heating rate is crucial to the homogenization process of the internal structure of the material. It can not only avoid a significant extension of the processing time due to slow heating (for example, the processing time may increase to 2-3 times the original when the heating rate is 1°C / min), but also prevent excessive internal stress of the material caused by excessive heating and produce defects such as cracks.
[0016] Further, in S3, the frequency of the ultrasonic generator generating ultrasonic waves is 28kHz-32kHz, and the power is set to 280W-350W.
[0017] Furthermore, in S3, the magnetic field frequency is 15kHz-25kHz, and the intensity is 500A / m-1000A / m.
[0018] The appropriate frequency can be selected according to the size and shape of the component. For example, if the plate size is 500mm×500mm×5mm, 30kHz and 350W power can be selected.
[0019] Furthermore, in S1, nitrogen is added in the form of manganese nitride, and the nickel content is greater than 8 wt %.
[0020] Further, the composite degaussing device includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit;
[0021] The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer. The ultrasonic generator is connected to the ultrasonic transducer. The ultrasonic generator is responsible for generating an electrical signal of a specific frequency and power. The electrical signal drives the ultrasonic transducer to generate ultrasonic waves. The ultrasonic transducers are distributed according to the shape of the component.
[0022] The electromagnetic field generating system includes a power supply and an electromagnetic coil. The power supply supplies power to the electromagnetic coil to generate an electromagnetic field with a specific frequency and strength. The electromagnetic coil is located inside the ultrasonic transducer. The electromagnetic coil is arranged according to the shape of the component. For example, for a plate component, the coil is reasonably distributed according to its plane shape to ensure uniform coverage of the electromagnetic field. For a rod component, a coil is arranged around the rod to ensure that the magnetic field is evenly distributed around the rod.
[0023] The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.
[0024] Specifically, the central processing unit uses intelligent algorithms to analyze data based on preset demagnetization target values (set according to different application scenarios, such as the target magnetic strength of high-end medical equipment housings is usually required to be less than 0.1Gs) and material characteristic parameters (such as the size and shape of the components, the initial magnetic strength after previous processing, etc.). Once it is found that the demagnetization effect of a certain area does not meet the expected standards, the system will automatically adjust the frequency (adjustment step of ±1kHz), power (adjustment step of ±50W), action time (adjustment step of ±5min) of the ultrasonic generator and the frequency (adjustment step of ±2kHz) and intensity (adjustment step of ±100A / m) of the electromagnetic field generation system to ensure that the demagnetization process of the entire component is uniform and can achieve the best effect.
[0025] Furthermore, the distribution of ultrasonic transducers is set according to the shape of the component, including array, plane matrix, and surround. For example, the array distribution is adopted for the plate for the shell, which can effectively cover a larger plane area of the plate; the plane matrix distribution is adopted for the thin plate, which is suitable for the thin plate structure to ensure energy uniformity; the surround distribution is adopted for the rod, which can make the rod uniformly energized in the circumferential direction.
[0026] Furthermore, for complex-shaped parts such as special-shaped shells, the layout of the ultrasonic transducer and the electromagnetic coil is designed according to their unique shape characteristics; if the surface of the shell is curved or has a concave-convex structure, the ultrasonic transducer and the electromagnetic coil are arranged in groups and zones, and they are divided into multiple groups. Each group supplies energy to different areas of the shell to ensure that every part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization.
[0027] Furthermore, for components with internal cavities, complex grooves or multiple irregular protrusions, the electromagnetic coil can be customized to a shape that matches the outer contour of the component. This allows the electromagnetic field to penetrate into every corner of the component. At the same time, ultrasonic transducers can be reasonably added at key locations, such as around the cavity, near the grooves, and at the connection between the protrusion and the main body. The two work together to achieve demagnetization.
[0028] Specifically, for stirring shaft components, if they have special blade shapes or non-circular cross-sections, in addition to adopting a surround layout, the distribution of ultrasonic transducers and electromagnetic coils can be further optimized. For example, in key areas where magnetic unevenness is prone to occur, such as the root of the blade, the transition area between the shaft and the blade, etc., the centralized supply of ultrasonic and electromagnetic field energy is strengthened to ensure that the magnetism of these special areas can also be effectively reduced and evenly distributed. Through such design and layout optimization, the method of the present invention can be applied to the demagnetization of various complex-shaped components, meeting the needs for demagnetization of complex-shaped austenitic stainless steel components in different application scenarios.
[0029] The present invention firstly precisely controls the composition of stainless steel, especially the content of nitrogen and manganese, stabilizes the austenite structure through the synergistic effect of nitrogen and manganese, effectively inhibits the formation of magnetic phases such as ferrite and martensite, and thus optimizes the initial magnetic properties of the material. Subsequently, the elements are fully dissolved and evenly distributed in the austenite matrix through solid solution treatment, further reducing the magnetism while maintaining other excellent properties of the material. The pressure wave generated by the ultrasonic wave, with its high frequency and high power characteristics, can effectively vibrate the magnetic particles in the magnetic medium, change the direction and distribution state of these particles, and then affect the magnetic field in the magnetic medium to achieve the demagnetization effect. Electromagnetic field demagnetization, on the other hand, is to apply an external electromagnetic field to cause the magnetic domains inside the magnetic material to rearrange. The magnetism of the magnetic material originates from the specific arrangement of its internal electron spin and magnetic domain. When the external magnetic field acts on the magnetic material, the magnetic domain will be reorganized accordingly, resulting in the enhancement of the material's magnetism. On the contrary, the demagnetization process is to adjust the arrangement of these magnetic domains to restore them to a relatively disordered state, thereby reducing or eliminating the magnetism of the material.
[0030] Ultrasonic demagnetization and electromagnetic field demagnetization start from the macroscopic physical vibration and microscopic magnetic domain arrangement respectively, and the two complement each other. When used together, electromagnetic field demagnetization can penetrate into the microscopic level of electron spin and magnetic domain arrangement, making up for the limitations of ultrasonic waves in adjusting these subtle structures, thereby significantly improving demagnetization efficiency. At the same time, the synergistic effect of ultrasonic demagnetization and electromagnetic field demagnetization can also ensure a more uniform demagnetization process and improve the overall processing quality.
[0031] Compared with the prior art, the efficient austenitic stainless steel demagnetization collaborative treatment method of the present invention has the following advantages:
[0032] 1. Efficient demagnetization and uniformity improvement
[0033] The present invention adopts a comprehensive method combining chemical composition regulation, solid solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment to effectively reduce the magnetic strength of 304 austenitic stainless steel. After treatment, the magnetic strength can be reduced to 0.03Gs-0.12Gs, and the demagnetization uniformity is good, which can meet the strict requirements of high-end equipment on magnetism, prevent magnetic interference with precision components, and ensure the normal operation of the equipment.
[0034] 2. Stable and optimized mechanical properties
[0035] The synergistic effect of each processing link stabilizes and optimizes the mechanical properties of the material. After treatment, the tensile strength is 520MPa-620MPa, the yield strength is 230MPa-260MPa, the yield and tensile strength are more consistent, and the surface quality of the components is good, meeting the requirements of strength and appearance accuracy in different high-end application scenarios.
[0036] 3. Corrosion resistance maintained
[0037] This comprehensive treatment method maintains the corrosion resistance of the material. The corrosion rate in a variety of corrosive environments is equivalent to that before treatment (about 0.04mm / a-0.06mm / a), ensuring the safety and reliability of the equipment in long-term use. It is suitable for medical, food processing and other equipment.
[0038] 4. Strong adaptability to complex shape parts
[0039] The distribution of the transducer and electromagnetic coil in the ultrasonic and electromagnetic field composite demagnetization treatment is adapted to components of different shapes, which can evenly reduce the magnetism of complex-shaped components (such as special-shaped housings, special structural parts, stirring shafts, etc.), overcome the shortcomings of traditional methods in demagnetizing complex components, and broaden the application range of materials.
[0040] 5. Significant advantages compared with traditional methods
[0041] Compared with the traditional thermal demagnetization method, the demagnetization effect of the present invention is more stable and the magnetic strength is greatly reduced, avoiding grain and stress problems; compared with the traditional AC demagnetization method, the demagnetization of plates and other components is more uniform and more accurate, significantly improving the competitiveness of 304 austenitic stainless steel in the high-end market. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0043] Figure 1 This is the microscopic morphology of the material used for the medical device housing in Example 1;
[0044] Figure 2 This is the microscopic morphology of the material used for the precision structural parts of the electronic equipment in Example 2;
[0045] Figure 3 This is the microscopic morphology of the material used for the food processing equipment component in Example 3;
[0046] Figure 4 This is the microscopic morphology of Example 1 using only the traditional AC demagnetization method;
[0047] Figure 5 This is the microscopic morphology of Example 2 using only the traditional thermal demagnetization method;
[0048] Figure 6 This is the microscopic morphology of Example 3 which adopts chemical composition regulation and solid solution treatment but does not perform ultrasonic demagnetization treatment. DETAILED DESCRIPTION
[0049] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0050] The present invention will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments.
[0051] Example 1: Special-shaped shell-like complex-shaped parts
[0052] Material selection: selected for high-end medical equipment with complex shaped parts such as special-shaped shells, which have extremely high requirements for magnetism, surface performance and overall reliability.
[0053] The degaussing collaborative processing method is:
[0054] S1. Chemical composition regulation
[0055] First, the chemical composition of the plate is accurately analyzed, and then nitrogen is added to it in the form of manganese nitride (MnN), and the nitrogen content is precisely controlled to 0.15wt%. At the same time, the manganese (Mn) content is precisely adjusted to 1.48wt%, and the nickel content is above 8wt%. Nitrogen and manganese work together to stabilize the austenite structure and inhibit the formation of magnetic phases such as ferrite and martensite, thereby optimizing the initial magnetic properties of the material for subsequent processing.
[0056] S2. Solution treatment
[0057] The plate regulated by S1 is placed in a high-precision vacuum heat treatment furnace and heated to 1150℃ at a heating rate of 4℃ / min. After reaching 1150℃, it is kept warm for 150min. During the insulation process, various elements (including nitrogen and manganese added in the form of manganese nitride) can be fully dissolved and evenly distributed in the austenite matrix, further reducing the magnetism while maintaining other excellent properties of the material. After the insulation, high-purity nitrogen is used to cool to room temperature at a cooling rate of 10℃ / s. This cooling method helps to obtain better strength while ensuring material properties and can effectively avoid the problem of excessive residual stress.
[0058] S3, ultrasonic and electromagnetic field composite demagnetization treatment
[0059] The plate after solution treatment is accurately placed in a special composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit;
[0060] The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer. The ultrasonic generator is connected to the ultrasonic transducer. The ultrasonic generator is responsible for generating an electrical signal of a specific frequency and power. The electrical signal drives the ultrasonic transducer to generate ultrasonic waves. The ultrasonic transducers are distributed according to the shape of the component.
[0061] The electromagnetic field generating system includes a power source and an electromagnetic coil. The power source supplies power to the electromagnetic coil so that it generates an electromagnetic field with a specific frequency and intensity. The electromagnetic coil is located inside the ultrasonic transducer and is arranged according to the shape of the component.
[0062] The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.
[0063] For complex-shaped parts such as special-shaped shells, the ultrasonic transducer and electromagnetic coil layout are designed according to their unique shape characteristics. The shell surface is curved or has concave-convex structures, and the ultrasonic transducer and electromagnetic coil are arranged in groups and zones. They are divided into multiple groups, and each group supplies energy to different areas of the shell to ensure that each part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization. The ultrasonic transducers can be distributed in arrays in each group.
[0064] Turn on the ultrasonic generator, adjust the frequency to 30kHz, and set the power to 350W; at the same time, start the electromagnetic field generation system, adjust the frequency to 20kHz, and set the intensity to 800A / m. Keep the ultrasonic and electromagnetic fields working together for 45 minutes. During the treatment process, use a high-precision magnetic sensor array to monitor the magnetic changes at different positions of the plate in real time. The central processing unit uses an intelligent algorithm to analyze and adjust the parameters of the ultrasonic generator and electromagnetic field generation system based on the preset target value and material characteristic parameters to ensure uniform demagnetization and achieve the best effect.
[0065] Effect:
[0066] The magnetic strength is significantly reduced and uniform: After testing, the magnetic strength of the treated plate is less than 0.12Gs, and the magnetism is uniform, which meets the strict requirements of high-end medical equipment shells for extremely low magnetism and magnetic uniformity, effectively preventing magnetism from interfering with precision components such as sensors inside the equipment, and ensuring the normal operation and high-precision performance of the equipment.
[0067] The mechanical properties are stable and the surface quality is good: the tensile test results show that the tensile strength of the treated material is 580MPa, the yield strength is 245MPa, the changes in yield strength and tensile strength are within ±3%, and there is no obvious damage and deformation on the surface of the treated plate. Figure 1 The microscopic morphology of the plate has a roughness variation within the range of ±0.2μm. This ensures the stability of the mechanical properties of the material during processing and use, meets the strength requirements of the medical device housing during installation and use, and ensures the appearance quality and assembly accuracy, and will not affect the overall appearance and performance of the equipment due to demagnetization.
[0068] Good corrosion resistance: Corrosion tests in a simulated human body fluid environment (corrosive solutions containing multiple ions) show that the corrosion rate is about 0.045mm / a, which is equivalent to that before treatment. This ensures the long-term stability of the material in the use environment of medical equipment, ensures the safety and reliability of the equipment during use, and does not affect the performance of the equipment due to corrosion.
[0069] Example 2 Materials for Precision Structural Parts of Electronic Equipment
[0070] Material selection: 304 stainless steel sheet with a size of 200mm×100mm×2mm is selected for precision structural parts in electronic equipment, such as metal brackets inside mobile phones, which have extremely high requirements for magnetism, flatness and dimensional accuracy.
[0071] The degaussing collaborative processing method is:
[0072] S1. Chemical composition regulation
[0073] After chemical composition analysis of the thin plate, manganese nitride was added to control the nitrogen content to 0.13wt%, the manganese content was adjusted to 1.46wt%, and the nickel content was above 8wt%.
[0074] S2. Solution treatment
[0075] The plate regulated by S1 was placed in a high-precision vacuum heat treatment furnace, heated to 1100°C at 3.5°C / min, kept warm for 100 min, and then cooled to room temperature with high-purity nitrogen at a cooling rate of 9°C / s.
[0076] S3, ultrasonic and electromagnetic field composite demagnetization treatment
[0077] The thin plate is placed in a composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit as in Example 1; wherein the ultrasonic transducer is distributed in a planar matrix, and the electromagnetic coil is arranged accordingly, and the electromagnetic coil is located on the inner side of the ultrasonic transducer. The frequency is adjusted to 28kHz, the power is 280W, the electromagnetic field frequency is set to 18kHz, the intensity is 600A / m, the action time is 50min, and the magnetic sensor array and the central processing unit are used for real-time monitoring and adjustment to ensure uniform demagnetization.
[0078] Effect:
[0079] Extremely low magnetism and high uniformity: The magnetic strength of the treated sheet is less than 0.03Gs, which meets the requirements of electronic equipment for extremely low magnetism, prevents magnetism from interfering with electronic components, and ensures the normal operation of the equipment.
[0080] Excellent flatness and dimensional accuracy: After processing, the flatness deviation of the thin plate is controlled within ±0.03mm, and the dimensional accuracy is within ±0.08mm. Figure 2 The microscopic morphology of the plate meets the high-precision requirements of precision structural parts in the assembly of electronic equipment and ensures the performance and reliability of the equipment.
[0081] Good mechanical properties: tensile strength is 570MPa, yield strength is 238MPa, and the yield strength and tensile strength vary within ±3%, ensuring the strength and stability of the structural parts during use.
[0082] Example 3 Materials for food processing equipment parts
[0083] Material selection: Select 304 stainless steel bars with a diameter of 30mm and a length of 300mm, which are used for parts such as stirring shafts in food processing equipment. They require low magnetism, high strength and good corrosion resistance to ensure the safety and hygiene of the food processing process.
[0084] The degaussing collaborative processing method is:
[0085] S1. Chemical composition regulation
[0086] After analyzing the chemical composition of the rod, manganese nitride was added to make the nitrogen content reach 0.16wt%, the manganese content was adjusted to 1.48wt%, and the nickel content was above 8wt%.
[0087] S2. Solution treatment
[0088] The rod was placed in a vacuum heat treatment furnace, heated to 1130°C at 4.5°C / min, kept at this temperature for 110 min, and then cooled to room temperature at 11°C / s using high-purity nitrogen.
[0089] S3, ultrasonic and electromagnetic field composite demagnetization treatment
[0090] The rod is placed in a composite demagnetization device, which includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit as in Example 1; wherein the ultrasonic transducer is arranged in a surrounding manner, and the electromagnetic coil is arranged around the rod. The frequency is set to 32kHz, the power is 320W, the electromagnetic field frequency is 22kHz, the intensity is 700A / m, and the action is for 35 minutes. The magnetic sensor array and the central processing unit are used to monitor and adjust to ensure uniform demagnetization effect.
[0091] Effect:
[0092] Low magnetism meets the requirements of food processing: the magnetic strength of the rod after treatment is less than 0.04Gs, which effectively prevents magnetic adsorption of metal impurities and ensures the purity and safety of the food processing process.
[0093] High strength and corrosion resistance: The tensile strength reaches 585MPa, the yield strength is 242MPa, and the yield strength and tensile strength change within ±2.5%. It has good corrosion resistance in the food processing environment, ensuring the long-term stable use of components such as the stirring shaft.
[0094] Good surface quality: The surface of the treated bar is smooth without obvious defects, easy to clean and maintain, and meets the hygiene standards of food processing equipment. Figure 3 The microscopic morphology of the rod.
[0095] Comparative Example 1 only uses chemical composition regulation
[0096] The same 304 stainless steel component as in Example 1 was selected and subjected to precise chemical composition analysis. Only nitrogen was added thereto in the form of manganese nitride (MnN), and the nitrogen content was precisely controlled at 0.15wt%. At the same time, the manganese (Mn) element content was precisely adjusted to 1.48wt%, and the nickel element content was above 8wt%. No subsequent solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment were performed.
[0097] Effect:
[0098] The reduction in magnetism is not obvious: Although the magnetic strength of the plate decreases to a certain extent through the regulation of chemical composition alone, the decrease is extremely limited compared with the magnetic strength after the complete processing flow, and the magnetic strength is still at a relatively high level (for example, the magnetic strength after treatment is between 2Gs-3Gs), which is far from meeting the requirements of high-end equipment for low magnetism.
[0099] Poor organizational stability: Due to the lack of solid solution treatment, the elements cannot be fully dissolved and evenly distributed in the austenite matrix, and the internal organizational structure of the material is uneven, which can easily lead to large local performance differences, and unstable performance may occur during subsequent processing and use. For example, when subjected to a certain external force or temperature changes, local deformation or performance changes may occur due to uneven organization, affecting the overall performance and service life of the equipment.
[0100] Mechanical properties are not optimized: Due to the lack of synergistic optimization of mechanical properties by solution treatment and demagnetization treatment, the mechanical properties of the material, such as tensile strength and yield strength, are relatively low (tensile strength is about 450MPa-500MPa, yield strength is about 180MPa-200MPa), and the strength consistency is poor, which cannot meet the requirements of high strength and stability for high-end application scenarios. In actual applications, it may not be able to withstand the stress during the operation of the equipment, increasing the risk of equipment damage.
[0101] From the perspective of microstructure, Figure 4(Micromorphology after treatment with chemical composition control method only) has significant differences compared with the previous three embodiments. In terms of phase composition, it is difficult to accurately control the element content by chemical composition control alone, resulting in incomplete stabilization of austenite structure, and a small amount of magnetic phase may be formed, especially in complex shape parts, which will lead to uneven magnetic distribution and fail to meet the requirements of high-end equipment for magnetic uniformity. In terms of grain morphology, due to the lack of solid solution treatment, the elements cannot be fully and evenly distributed, the grain growth is not optimized, the grains are of different sizes and uneven growth, which affects the mechanical properties, stability and demagnetization uniformity of the material. In terms of magnetic domain structure, there is a lack of coordination between solid solution treatment and composite demagnetization treatment, the magnetic domain arrangement is difficult to effectively adjust, the structure is chaotic, the magnetic strength is reduced to a limited and uneven level, and the low magnetism and high uniformity standards of high-end equipment cannot be met, affecting the stability and normal operation of the equipment magnetic field environment. It can be seen that the comprehensive treatment method of the present invention has obvious advantages in optimizing the microstructure of materials and improving performance. It is difficult to meet the strict requirements of high-end applications for materials using only chemical composition control methods.
[0102] Comparative Example 2: Only using solution treatment demagnetization method
[0103] Processing process: The 304 stainless steel component identical to that in Example 1 is heated to 1050°C and then cooled naturally in ordinary air. This is the conventional operation mode of the traditional thermal demagnetization method.
[0104] Effect (insufficient performance after air cooling):
[0105] Poor and uneven demagnetization effect: The demagnetization effect is poor, and the magnetic strength fluctuates between 4-8Gs, which is much higher than the demagnetization level in the embodiment of the present invention and cannot meet the high-end application scenarios with strict magnetic requirements. Moreover, this treatment method leads to uneven grain growth, coarse grains in some areas, and obvious residual stress, which makes the magnetic distribution inside the material uneven, further affecting the stability of the demagnetization effect.
[0106] Degradation of mechanical properties: The mechanical properties of the material after treatment are seriously affected, with the tensile strength reduced by about 11% and the yield strength reduced by about 13%. In the subsequent processing, the tool wears seriously and the surface roughness increases, which cannot meet the requirements of high-end medical equipment shells for material strength and surface quality. For example, in actual processing, it may be necessary to replace the tool more frequently, increasing production costs. At the same time, the surface quality after processing is difficult to meet the requirements of high-precision equipment, affecting the overall performance and appearance of the equipment.
[0107] Corrosion resistance may be affected: Due to changes in grain structure and residual stress, there may be a potential impact on the corrosion resistance of the material. Although no specific test has been conducted, judging from the changes in the material's microstructure, its stability when used in a corrosive environment for a long time may not be as good as the material treated with the combination of the present invention.
[0108] Figure 5 The microscopic morphology after only using the solution treatment demagnetization method (traditional thermal demagnetization method) is significantly different from the first three examples. In Examples 1-3, the chemical composition is regulated to stabilize the austenite structure, and the solution treatment uses appropriate parameters to evenly distribute the elements and promote uniform and fine grain growth. Multiple treatments work together to achieve low and uniform magnetism and a complete microstructure. Figure 5 ) The grains grow unevenly and some are coarse, which cannot be effectively controlled due to natural cooling; the magnetic strength is high and fluctuates greatly, the demagnetization is uneven, and it is difficult to adjust the magnetic domain structure by natural cooling; there are obvious signs of residual stress and the microstructure may be distorted and deformed, which affects the magnetic properties, mechanical properties and corrosion resistance.
[0109] Comparative Example 3: Electromagnetic field demagnetization method only
[0110] Treatment process: The 304 stainless steel component identical to that in Example 1 was placed in an alternating magnetic field, and the magnetic intensity was gradually reduced to zero at a rate of 10 Gs / min.
[0111] Effect:
[0112] Uneven demagnetization and limited degree: For parts with relatively large size and certain complex shapes (edges and other parts) such as special-shaped shells, the demagnetization effect is uneven. The difference in magnetic strength between the edge and the center of the plate can reach more than 6Gs. The magnetic strength of the treated material can only reach about 1.8Gs at the lowest, which is far from the low magnetic level in the embodiment of the present invention. It cannot meet the strict requirements of high-end medical equipment for magnetic accuracy and may affect the normal operation of components such as sensors inside the equipment.
[0113] Unable to optimize the internal structure of the material: The traditional AC demagnetization method only reduces magnetism through an alternating magnetic field, and cannot improve the internal structure of the material like the solution treatment in the present invention. Therefore, it is not possible to optimize other properties of the material while reducing magnetism, such as mechanical properties and corrosion resistance. This means that although the magnetism of the material is reduced after AC demagnetization treatment, the comprehensive performance in practical applications is still insufficient and cannot meet the multi-faceted requirements of high-end fields for materials.
[0114] Figure 6 The microscopic morphology after only electromagnetic field demagnetization treatment is shown. Compared with the first three examples, there are obvious differences in microstructure. From the perspective of grain morphology and distribution, the grains in Examples 1-3 are uniform and fine. This is because the chemical composition is used to regulate the austenite structure, and the solid solution treatment promotes the uniform distribution of elements and thus makes the grains grow uniformly. Figure 6) The grain growth is uneven, and the grains in some areas are coarse. Due to the lack of optimization steps such as solid solution treatment, alternating magnetic field demagnetization alone cannot effectively regulate the grain growth. In terms of magnetic-related characteristics, the magnetic strength of Examples 1-3 is low and uniform. The synergistic effect of multiple treatment methods enables chemical composition regulation to inhibit the formation of magnetic phases, solid solution treatment to reduce magnetism, and ultrasonic and electromagnetic field composite demagnetization treatment to ensure uniform and significant demagnetization, while Comparative Example 3 ( Figure 6 ) The magnetic strength is high and the difference between the edge and the center of the plate is large. The alternating magnetic field demagnetization is difficult to adjust the magnetic domain structure in depth due to the uneven magnetic field distribution of complex shape parts, resulting in poor demagnetization effect. As for the magnetic domain structure, the magnetic domain structure of Examples 1-3 is orderly after a series of treatments, which is conducive to performance optimization, while Comparative Example 3 ( Figure 6 ) Due to the lack of collaborative treatment means, the uneven distribution of the magnetic field causes the magnetic domains to be adjusted to different degrees and present a chaotic state, which affects the magnetic properties, mechanical properties and corrosion resistance of the material. In summary, the differences in the microstructure of the treatment method using only the electromagnetic field demagnetization method make it impossible to achieve the good results in the embodiment, reflecting the advantages of the collaborative treatment method of the present invention.
[0115] Comparative Example 4: Chemical composition control and solution treatment without ultrasonic and electromagnetic field composite demagnetization treatment
[0116] Processing process:
[0117] The 304 stainless steel parts are treated according to the chemical composition control and solution treatment steps in Example 1, that is, the plate is first accurately analyzed for chemical composition, and then nitrogen is added thereto in the form of manganese nitride (MnN), and the nitrogen content is accurately controlled at 0.15wt%, and the manganese (Mn) element content is accurately adjusted to 1.48wt%, and the nickel element content is above 8wt%. Then, the plate with chemical composition control is placed in a high-precision vacuum heat treatment furnace, heated to 1150°C at a heating rate of 4°C / min, and kept warm for 150min after reaching 1150°C. After the insulation is completed, high-purity nitrogen is used to cool to room temperature at a cooling rate of 10°C / s. No ultrasonic and electromagnetic field composite demagnetization treatment is performed after treatment.
[0118] Effect
[0119] The degree of reduction in magnetism is limited: after chemical composition regulation and solution treatment, the magnetic strength of the plate is reduced, but it is still higher than the magnetic strength after the complete combination treatment (for example, the magnetic strength after solution treatment in Example 1 is lower than 0.5Gs, but it does not reach the level of lower than 0.12Gs after ultrasonic and electromagnetic field composite demagnetization treatment in Example 2). It cannot meet high-end application scenarios with more stringent requirements on magnetism, such as high-end electronic semiconductor manufacturing fields. In these fields, even lower magnetism may affect equipment performance.
[0120] Poor uniformity: Due to the lack of uniformity of ultrasonic and electromagnetic field composite demagnetization treatment, there are certain differences in the magnetic strength of different parts of the plate, and relatively high magnetism may appear in some local areas, which is not satisfactory for high-end equipment components that require extremely high magnetic uniformity. For example, in some key structural parts of precision electronic equipment, uneven magnetism may cause magnetic field interference, affecting the normal operation and performance stability of the equipment.
[0121] Comparative Example 5: S3 only uses ultrasonic demagnetization
[0122] The difference from Example 1 is that only ultrasonic demagnetization is used, and the rest is the same as Example 1.
[0123] Effect: The magnetic intensity is low, about 0.5Gs, but the uniformity is poor, and relatively high magnetism appears in some local areas.
[0124] Comparative Example 6: S3 only uses electromagnetic field demagnetization
[0125] The difference from Example 1 is that only electromagnetic field demagnetization is used, and the rest is the same as Example 1.
[0126] Effect: The magnetic intensity is low, about 0.8Gs, but the uniformity is poor, and relatively high magnetism appears in some local areas.
[0127] Comparative Example 7: Different chemical composition control parameters
[0128] A—High ratio of nitrogen and manganese: The difference from Example 1 is that the nitrogen content is 0.25wt%, the manganese (Mn) element content is 1.8wt%, and the rest is the same as Example 1.
[0129] Effect: The magnetic strength is reduced, but not as good as that in Example 1, about 0.3 Gs, and the tensile effect is relatively poor. The tensile strength of the treated material is 501 MPa, the yield strength is 212 MPa, and slight cracks can be seen in the microscopic morphology, which does not meet the use requirements.
[0130] B—Low ratio of nitrogen and manganese: The difference from Example 1 is that the nitrogen content is 0.08wt%, the manganese (Mn) element content is 1.2wt%, and the rest is the same as Example 1.
[0131] Effect: The magnetic strength is reduced, but not as good as that in Example 1, about 0.4 Gs, and the tensile effect is good. The tensile strength of the treated material is 535 MPa and the yield strength is 229 MPa.
[0132] Comparative Example 8: Different heating rates of solution treatment
[0133] A- Low heating rate: The difference from Example 1 is that the heating rate is 1°C / min to 1150°C, and the rest is the same as Example 1.
[0134] Effect: After treatment, the magnetic strength of the parts is between 1-2Gs, and there is still weak magnetism in some local areas on the surface of the material. This is because the heating rate is too slow and the austenitization inside the organization is uneven, resulting in uneven demagnetization.
[0135] B- low and high heating rate: the difference from Example 1 is that the heating rate is 6°C / min to 1150°C, and the rest is the same as Example 1.
[0136] Effect: After treatment, the magnetic strength of the parts is between 1-4Gs, and there is still weak magnetism in some areas of the material surface, with large magnetic differences. This is due to the rapid heating rate and uneven austenitization inside the organization, which leads to uneven demagnetization. In addition, due to the rapid heating rate, the internal stress of the material is too large, resulting in cracks and other defects.
[0137] Comparative Example 9: Different composite demagnetization parameters
[0138] A-ultrasonic wave and magnetic field parameters are lower than the range values: the difference from Example 1 is that the frequency of the ultrasonic generator is 25kHz, and the power is set to 250W; the frequency of the electromagnetic field is adjusted to 10kHz, and the intensity is set to 450A / m, and the rest is the same as Example 1.
[0139] Effect: After treatment, the magnetic strength of the parts is between 0.6-2.5Gs, and there is still weak magnetism in some local areas on the surface of the material. This may be because the ultrasonic and magnetic field parameters are lower than the required range, resulting in the energy of the ultrasonic and magnetic fields not being able to reach the inside of the material evenly, resulting in uneven demagnetization.
[0140] B- Ultrasonic wave and magnetic field parameters are higher than the range values: The difference from Example 1 is that the frequency of the ultrasonic generator is 35kHz, and the power is set to 400W; the frequency of the electromagnetic field is adjusted to 30kHz, and the intensity is set to 1200A / m, and the rest is the same as Example 1.
[0141] Effect: After treatment, the magnetic strength of the parts is between 0.3-1.8Gs, and there is still weak magnetism in some local areas on the surface of the material. If the ultrasonic and magnetic field parameters are too large, the demagnetized material will regain its magnetism.
[0142] By comparing the above embodiments with the comparative examples, it is found that the present invention adopts a combination of chemical composition regulation, solid solution treatment and ultrasonic and electromagnetic field composite demagnetization treatment to effectively reduce the magnetic strength of 304 austenitic stainless steel, and the demagnetization uniformity is good, which can meet the strict requirements of high-end equipment on magnetism, prevent magnetic interference with precision components, and ensure the normal operation of the equipment.
[0143] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A highly efficient austenitic stainless steel demagnetization collaborative treatment method, characterized in that: The method comprises the following steps: S1. Chemical composition regulation Conduct precise chemical composition analysis on 304 austenitic stainless steel, control the nitrogen content to 0.1-0.2wt%, and the manganese content to 1.4-1.5wt%; S2. Solution treatment The 304 austenitic stainless steel regulated by S1 is placed in a vacuum heat treatment furnace to increase the temperature, and then kept warm after reaching the target temperature; After the insulation is completed, high-purity nitrogen is used for rapid cooling; S3, ultrasonic and electromagnetic field composite demagnetization treatment Place the 304 austenitic stainless steel treated with S2 in a composite demagnetization device with ultrasound and electromagnetic field. Select the appropriate ultrasonic transducer and electromagnetic coil layout according to the shape of the component to ensure that the ultrasound and electromagnetic field energy evenly cover the component and keep the ultrasound and electromagnetic field working together for 30min-50min.
2. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: In S2, the temperature is raised to 1050°C-1150°C at a heating rate of 3.5°C / min-4.5°C / min and kept at this temperature for more than 90 minutes.
3. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: In S2, the cooling rate is 8°C / s-12°C / s.
4. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: In S3, the frequency of the ultrasonic generator generating ultrasonic waves is 28kHz-32kHz, and the power is set to 280W-350W.
5. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: In S3, the magnetic field frequency is 15kHz-25kHz and the intensity is 500A / m-1000A / m.
6. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: In S1, nitrogen is added in the form of manganese nitride, and the nickel content is more than 8 wt%.
7. The high-efficiency austenitic stainless steel demagnetization collaborative treatment method according to claim 1 is characterized in that: The composite demagnetization device includes an ultrasonic generating system, an electromagnetic field generating system, a magnetic sensor array and a central processing unit; The ultrasonic generating system includes an ultrasonic generator and an ultrasonic transducer, the ultrasonic generator is connected to the ultrasonic transducer, and the ultrasonic transducers are distributed according to the shape of the component; The electromagnetic field generating system includes a power supply and an electromagnetic coil, and the electromagnetic coil is located inside the ultrasonic transducer; The magnetic sensor array is set close to the surface of the component to monitor the magnetic changes at different positions of the component in real time and transmit the data to the central processing unit. The central processing unit adjusts the frequency of the ultrasonic generator, the power of the ultrasonic wave, the ultrasonic action time, the magnetic field frequency, the magnetic field strength and the magnetic field action time according to the demagnetization effect.
8. The high-efficiency austenitic stainless steel demagnetization coordinated treatment method according to claim 7, characterized in that: The distribution modes of ultrasonic transducers include array, planar matrix and surround.
9. The high-efficiency austenitic stainless steel demagnetization coordinated treatment method according to claim 7, characterized in that: For complex-shaped parts such as special-shaped shells, the layout of ultrasonic transducers and electromagnetic coils is designed according to their unique shape characteristics; if the surface of the shell is curved or has concave-convex structures, the ultrasonic transducers and electromagnetic coils are arranged in groups and zones. Divide them into multiple groups, and each group supplies energy to different areas of the shell to ensure that every part of the shell can obtain sufficient ultrasonic and electromagnetic field energy, thereby achieving uniform demagnetization.
10. The high-efficiency austenitic stainless steel demagnetization coordinated treatment method according to claim 7, characterized in that: For components with internal cavities, complex grooves or multiple irregular protrusions, the electromagnetic coil can be customized to a shape that matches the contour of the component, and ultrasonic transducers can be reasonably added at key locations, such as around the cavity, near the grooves, and at the connection between the protrusion and the main body.